Kemampuan Mahasiswa Berkomunikasi Lisan Melalui Proses Belajar Mengajar - Hari Suryaningrum, Diah; Takarini, Nurjanti (Jurnal Riset Ekonomi dan Bisnis, 2007)
Basically improvement effort of competency and lecturer professionality becoming main attention of Higher Education Directorate General (Ditjen DIKTI). This thing based on conception that lecturer is one of a real important component in learning process, and directly influences improvement of quality of learning process for student. In working professionally, faculty of economics graduate hardly requires ability to oral communication. This research purpose to analyze ability of learning process in the effort increasing ability to oral communication of students. Ability to oral communication will be proxy without existence of fear in communicating.Base on research purpose, primary data applied in this research. Research population are junior students on academic year 2006/2007 and senior students which has gone through more than 120 sks. Both consist of economic development, economic management, & economic accountancy study program. The number of the students are noted about 636 junior and 738 senior students. From this two sub population amounts which not homogeneous, selected 468 students as sample base on Slovin formula and by using probability sampling technique. As respondent, the students are met when they are present in campus and not receiving lesson, during research period. Only 427 units data which can be analyzed by using ANOVA. Result of research indicates that there is no difference level of fear to oral communication between junior students with senior student. Under assumption that junior students and senior student as homogeneous population, then this result can concluded that learning process can increase ability of oral communication of students.Keywords: Oral Communication, Learning Process